Residual effect of organic amendments on growth, productivity, economics and agri-energetics of local popcorn (Zea mays everta) in toria (Brassica campestris) – popcorn cropping system under mid hills of Sikkim Himalayas - SINGH, RAGHAVENDRA; BABU, SUBHASH; AVASTHE, R K; SINGH, M; YADAV, G S; CHETTRI, TIRTHA KUMARI (The Indian Journal of Agricultural Sciences, 2018)
Under organic management condition, it is presumed that the nutrients applied to preceding crops exhibits the considerable effect on succeeding crops, hence a fixed plot field experiment was conducted during three years (2011 to 2014) at Research Farm, National Organic Farming Research Institute (NOFRI), Tadong, Gangtok to assess the residual effect of mulching and vermicompost on growth, productivity, profitability and energetics of popcorn (Zea mays everta) under toria (Brassica campestris)-popcorn cropping system. The results revealed that the mulching materials applied to the preceding crops exhibited significant residual effect on growth, yield attributes and grain yield of succeeding popcorn over non-mulching (bare soil). However, among the mulching materials, rice straw mulch @ 5 t/ha exerted maximum residual effect and resulted in higher cob length (16.0 cm), cob girth (12.0 cm), grain yield (1.93 ha), stover yield (3.07 t/ha), net returns (72.8 × 103 rs.`/ha), B:C ratio (2.87) and energy use efficiency (20.62%) of popcorn. With regards to the vermicompost levels, residual effect of vermicompost @ 1.5 t/ha recorded the maximum grain yield (1.9 t/ha), net returns (71.3× 103 rs.`/ha), B:C ratio (2.81) and energy use efficiency (20.34%) of the succeeding popcorn under toria-popcorn cropping system.